Kepatuhan Penggunaan Obat Asma Terhadap Kualitas Hidup Pasien Asma Rawat Jalan Rumah Sakit X Gorontalo - Teti Sutriyati Tuloli; Nur Rasdianah; Sitti Nurul Wildan Basrudin (State University of Gorontalo, 2023)
Asthma, a chronic disease, is characterized by the inflammation in the respiratory tract, followed by coughing, wheezing, and difficulty breathing. This cross-sectional research was intended to explore the effect of medical compliance on the quality of life of outpatients with asthma. It employed a non-experimental analysis. All 30 respondents were outpatients visiting Gorontalo x hospital they were selected purposively. The compliance level was examined using a relevant questionnaire, while the quality of life was examined using Mini-AQLQ questionnaire. The result of the chi-square test, revealing that 95% of confidence interval; ? = 0.05, where p 0.405 (p ?) OR 2.216, suggesting that the medical compliance did not affect the quality of life. One can argue that this notion, thereby, signifies the necessity to view the quality of life of patients with asthma as a complex issue from multiple perspectives